An Unusual False-Positive Uptake of Radioiodine Caused by Posttraumatic Superficial Scab. (2nd April 2022) - Xiao, Liu; Jiang, Lisha; Huang, Rui; Tian, Rong; Liu, Bin
Abstract: A 22-year-old man with a history of recurrent papillary thyroid cancer underwent 131 I therapy. Posttherapeutic whole-body scintigraphy was performed 5 days after administration of 5.5 GBq of 131 I. The scintigraphy revealed increased activity in the left elbow. On physical examination, the patient had posttraumatic superficial scab at the site of the abnormal activity.